Financial integration and credit democratization: Linking banking deregulation to economic growth - Berger, Elizabeth A.; Butler, Alexander W.; Hu, Edwin; Zekhnini, Morad (Journal of Financial Intermediation, 2021)
We use a matching method that constructs synthetic counterfactual states to identify the channels that link bank deregulation to financial integration, and thereby to economic growth. We document a positive, but conditional, effect of financial integration on economic growth. We explore the heterogeneous effects of financial integration across states depending on the capital mobility in each state. Our results reveal a correlation between financial integration and subsequent banking sector changes related to an expansion in loan recipients. We show that financial integration democratizes lending and spurs economic growth.